2020
DOI: 10.1155/2020/5046832
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Repair and Orthodromic and Antidromic Nerve Grafts: An Experimental Comparative Study in Rabbit

Abstract: Purpose. Although many surgeons have anecdotally described reversing the polarity of the autograft with the intent of improving regeneration, the optimal orientation of the autogenous nerve graft remains controversial. The aim of this study was to compare (1) the outcomes of orthodromic and antidromic nerve grafts to clarify the effect of nerve graft polarity and (2) the outcome of either form of nerve grafts with that of nerve repair. Methods. In 14 of the 26 rabbits used in this study, a 1 cm defect was made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The topic on normal or reverse proximodistal orientation of autologous nerve grafts has been discussed for many decades and the conclusion has been well known by microsurgeons. Although previous animal studies have shown that proximodistal orientation has no impacts on nerve regeneration and functional recovery (Afshari et al, 2018; Kim et al, 2020; Nakatsuka et al, 2002; Sanders & Young, 1942; Sotereanos et al, 1992; Stromberg et al, 1979), many surgeons anecdotally reverse autograft orientation with the intent of improving nerve regeneration (Roberts et al, 2017). Furthermore, nerve autograft is the gold standard for repair of nerve injuries with gaps, accordingly this topic is still of value among microsurgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic on normal or reverse proximodistal orientation of autologous nerve grafts has been discussed for many decades and the conclusion has been well known by microsurgeons. Although previous animal studies have shown that proximodistal orientation has no impacts on nerve regeneration and functional recovery (Afshari et al, 2018; Kim et al, 2020; Nakatsuka et al, 2002; Sanders & Young, 1942; Sotereanos et al, 1992; Stromberg et al, 1979), many surgeons anecdotally reverse autograft orientation with the intent of improving nerve regeneration (Roberts et al, 2017). Furthermore, nerve autograft is the gold standard for repair of nerve injuries with gaps, accordingly this topic is still of value among microsurgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Ansselin and Davey provided the theoretical basis of this belief by showing that reverse‐oriented autografts promoted axonal regeneration better than normally oriented autografts in a rat sciatic nerve model (Ansselin & Davey, 1988; Ansselin & Davey, 1993). However, other animal studies have not shown differences between the normal or reversed orientations of autografts in functional and histological analyses (Afshari et al, 2018; Kim et al, 2020; Nakatsuka et al, 2002; Sanders & Young, 1942; Sotereanos et al, 1992; Stromberg et al, 1979).…”
Section: Introductionmentioning
confidence: 98%
“…Most studies did not nd signi cant differences between normally or reverse-oriented autografts [5][6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…In total, eight animal studies using rat or rabbit models have been performed to investigate the effect of autograft orientation on neural and functional regeneration during interpositional nerve grafting, with most conducted >2-3 decades ago [3][4][5][6][7][8] . Recent studies have used advanced tools to assess outcomes after autografting, including immunohistochemical staining of cross-sectioned nerves using antibodies against choline acetyltransferase or NF, and diffusion tensor imaging of the nerve 9,10 . In our study, we used behavioral evaluation of sciatic nerve function, morphometric analysis using immunohistochemicalstained cross-sectioned and whole-mount nerves, and morphometric analysis using H&E-stained crosssectioned muscles to investigate the effect of autograft orientation on nerve regrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation